3D Mineralogy, Texture And Damage Analysis Of Multiphase Mineral Particles With A High Contrast, Submicron Resolution X-Ray Tomography System - S. H. Lau (International Mineral Processing Congress, 2012)
Rapid 3D characterization of multiphase mineral particles in a variety of mineral processing applications is described, including: mineral liberation analysis, grain size, mineral exposure analysis, particle damage, and pore network structure for fluid flow simulation in heap leaching. While micro X-ray computed tomography systems (microCTs) have been used for many years, industrial adoption is limited due to a variety of reasons, including insufficient resolution, the general lack of imaging contrast to differentiate different mineral phases within a multiphase mineral particle and the lack of automated 3D mineral processing software. For example, resolution with industrial CTs and desktop microCT is of the order of tens of microns to a few microns at best, depending on specimen size and CT configuration. We describe a novel lab-based X-ray microscope, XRM, which overcomes these resolution and contrast limitations, notably as the industry is going towards finer grains and more complex ore bodies. Using lens-based optics and detectors (similar to its XRM counterpart in synchrotron beam lines), resolution of the lab based system is in the submicron range with contrast better than conventional microCTs. Hence, visualization, differentiation and segmentation of most mineral phases of interest to the industry are now feasible. Coupling these high resolution and high contrast tomography images with a suite of customized 3D segmentation algorithms and analysis software, applications in mineral liberation analysis for process control, particle damage assessment and other mineral processing applications can be achieved. This non invasive 3D technique which requires relatively little sample preparation is currently being considered for coal, industrial minerals, and base/precious metal ores, complementing existing microscopy techniques such as QEMSCAN and MLA for a variety of applications